على بعض الخواص الحرارية والميكانيكية لعجينة السمنت البورتالاندي PTFE دراسة تأثير إضافة حبيبات بوليمر - جرجـيس, إيـاد جيـاد (Al-Nahrain Journal of Science, 2013)
In this study, the effect of adding polymer grains (PTFE)- with different concentrations 2%, 4%, 6% and 8% of the weight of the samples which have been made- on the thermal conductivity coefficient and compressive resistivity of Portland cement paste that used in the building has been investigated. The thermal conductivities of the samples have been measured by using Lee-disk; while the compressive resistivities have been found by using Universal machine. The results indicate that the addition of the polymer grains (PTFE) lead to enhance the ability of thermal insulation via decreasing the value of the thermal conductivities of the samples; while adding of these grains of polymers lead to decrease in the mechanical properties values which is presented by compressive resistivity. The ideal concentrations of the polymer grains which have good thermal insulations have been specified without the high effects of the mechanical properties.